The dynamics of english language use among Malaysian bloggers: Perception of TESL students at Universiti Kebangsaan Malaysia. - Ramlee Mustapha; Lydia Wong Su Mei (Pusat Perkembangan Pelajar ,U.K.M, 2009)
Blogs are now marking a new mode of communication, making impact on domains such as virtual formation of speech communities, knowledge-sharing, pedagogical implication as well as formation of virtual identity. It is estimated that more than three billion websites in the world today and more than 70 million are blogs. In Malaysia, it is estimated that half a million blogs existed. Language used by bloggers could reflect the unique pattern of discourse within the blogosphere where the combination of both monologue and dialogue in a space-bound, digital environment is observed. Some studies show that a strong sense of identity is seen within the literacy practices in blogosphere where bloggers tend to use code-switching and code mixing in their blogs. Thus, the purpose of this study was to examine the dynamics of English language use among top-ranked Malaysian bloggers from the perception of final-year TESL undergraduate students. The study reveals that there are various linguistic features found in blogs and also in the interaction with one another in meaning-making process. Several implications are discussed.